Egg cortisol treatment affects the behavioural response of coho salmon to a conspecific intruder and threat of predation. (June 2015) - Sopinka, Natalie M.; Hinch, Scott G.; Healy, Stephen J.; Harrison, Philip M.; Patterson, David A.
Abstract : Knowledge continues to emerge on how maternally derived egg hormones influence progeny behaviour in oviparous taxa. Of particular interest is how glucocorticoids (GCs) in eggs, as a signal of maternal stress, affect offspring behavioural traits. To date, research has focused on effects of egg GCs on offspring behaviours within a single experimental context. Little is known regarding how egg GCs affect relationships among behaviours and across ecological contexts (i.e. behavioural syndromes). We explored how exogenously increased egg cortisol shapes behavioural syndromes of juvenile coho salmon, Oncorhynchus kisutch . Social dominance during a territory intrusion and boldness following a simulated predator attack were recorded for juvenile coho salmon reared from cortisol-treated and untreated eggs. When exposed to a conspecific intruder, coho salmon treated with cortisol in ovo increased dominance behaviours, whereas coho salmon reared from untreated eggs reduced these behaviours. Following exposure to a simulated predator attack, coho salmon reared from cortisol-treated eggs increased boldness (i.e. increased activity and feeding; reduced shelter use), whereas coho salmon reared from untreated eggs reduced boldness. A dominance–boldness relationship was observed for coho salmon reared from cortisol-treated, but not untreated, eggs; dominance during the territory intrusion positively correlated with boldness under threat of predation. Our results highlight the complex influence of egg GCs on offspring behaviour and behavioural syndromes. Continued investigation into the outcomes of egg GCs on offspring will broaden our understanding of intergenerational components of the hormone–behaviour nexus. Highlights: Salmon eggs were treated with cortisol and progeny were assessed for dominance and boldness. Progeny response to an intruder and predation threat varied between egg treatments. Egg cortisol treatment generated a dominance–boldness behavioural syndrome.